Single nucleotide polymorphism of PIK3CA and its interaction with the environment are risk factors for Chinese Han ovarian cancer - Zhang, Hui; Zhou, Li (Pathology, research and practice, 2019)
The PI3K pathway is an important signaling network that regulates key cell functions such as cell growth, proliferation and survival. PIK3CA mutations are found in a variety of human cancers. This study aimed to analyze the effect of interactions between PIK3CA rs2699887, rs3976507, rs6443626 single nucleotide polymorphisms (SNPs), and the environment on the risk of Chinese Han ovarian cancer. Sanger sequencing was used to analyze the PIK3CA rs2699887, rs3976507, rs6443626 genotypes in 350 Chinese Han ovarian cancer patients and 350 control individuals, and the expression of PIK3CA protein was detected in 117 ovarian cancer patients. In subjects with age ≥60 years, Number liveborn ≤ 3, no smoking, no alcohol, and no family history of ovarian cancer, the risk of ovarian cancer of the rs2699887 T allele carriers were increased (all p < 0.05). In subjects with obesity (BMI ≥ 24 kg/m2), Number liveborn ≤3, no smoking, no alcohol, and no family history of ovarian cancer, the risk of ovarian cancer of rs3976507 T allele carriers and rs6443626 C allele carriers were increased (all p < 0.05). PIK3CA protein expression level in PIK3CA rs2699887 C > T, rs3976507 C > T, rs6443626 T > C locus homozygotes was significantly higher than that in heterozygotes (p <  0.05). Interaction between PIK3CA rs2699887 SNP and age, number of liveborn, tobacco, alcohol, a family history of ovarian cancer and other factors are associated with ovarian cancer risk. Interaction between PIK3CA rs3976507 and rs6443626 loci, and factors such as BMI, number of liveborn, tobacco, alcohol, and family history of ovarian cancer are associated with ovarian cancer risk.